Occurrence of rabies in wolf (Chrysocyon brachyurus, Illiger 1815) - Silva, Renato Augusto da; Breckenfeld, Silvio Guilherme B. (Pesquisa Agropecuaria Brasileira, 2014)
Rabies virus was isolated from brain and submaxillary gland of three wolves in conditions of captivity. The occurrence of rabies was determined by the appearance of Negri bodies in the brains of the wolves and verified by intercerebral inoculation of adult mice. One of the samples of virus was neutralized by an anti-rabies serum of known neutralizing capability.